Training of doctors of non-specialized health care institutions to provide assistance to people with mental disorders based on the training developed by WHO on the clinical management of mental disorders under the mhGAP program - Карпенко, Марина (Psychosomatic Medicine and General Practice, 2023)
This text is the abstract for the qualifying graduation thesis on the topic "Training of doctors of non-specialized health care institutions to provide assistance to people with mental disorders based on the training developed by WHO on the clinical management of mental disorders according to the mhGAP program." The following is devoted to the importance of training family physicians in the skills of working with the mentally ill.